Habitat Split as a Cause of Local Population Declines of Amphibians with Aquatic Larvae - Becker, C. Guilherme; Fonseca, Carlos R.; Haddad, Celio Fernando Baptista [UNESP]; Prado, Paulo I. (Wiley-Blackwell Publishing, Inc, 2010)
Most amphibian species have biphasic life histories and undergo an ontogenetic shift from aquatic to terrestrial habitats. In deforested landscapes, streams and forest fragments are frequently disjunct, jeopardizing the life cycle of forest-associated amphibians with aquatic larvae. We tested the impact of habitat split-defined as human-induced disconnection between habitats used by different life-history stages of a species-on four forest-associated amphibian species in a severely fragmented landscape of the Brazilian Atlantic Forest. We surveyed amphibians in forest fragments with and without streams (referred to as wet and dry fragments, respectively), including the adjacent grass-field matrix. Our comparison of capture rates in dry fragments and nearby streams in the matrix allowed us to evaluate the number of individuals that engaged in high-risk migrations through nonforested habitats. Adult amphibians moved from dry fragments to matrix streams at the beginning of the rainy season, reproduced, and returned at the end of the breeding period. Juveniles of the year moved to dry fragments along with adults. These risky reproductive migrations through nonforested habitats that expose individuals to dehydration, predation, and other hazards may cause population declines in dry fragments. Indeed, capture rates were significantly lower in dry fragments compared with wet fragments. Declining amphibians would strongly benefit from investments in the conservation and restoration of riparian vegetation and corridors linking breeding and nonbreeding areas.
Keywords: amphibian declines; biodiversity; conservation planning; forest fragmentation; habitat split; life-history traits; matrix habitat; riparian vegetation